2020
DOI: 10.1186/s12909-020-02156-8
|View full text |Cite
|
Sign up to set email alerts
|

The development of a framework of entrustable professional activities for the intern year in Ireland

Abstract: Background: Entrustable Professional Activities (EPAs) are units of professional practice that capture essential competencies in which trainees must become proficient before undertaking them independently. EPAs provide supervisors with a solid justification for delegating an activity to trainees. This study aimed to develop and ensure face validity of a set of EPAs for junior doctors in the first year of clinical practice in the Republic of Ireland. Methods: An iterative eight stage consensus building process … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 32 publications
0
23
0
Order By: Relevance
“…Overview of sample: A total of 57 participants initiated the survey, with 49 fully completing it, yielding a completion rate of 86%. The responders covered all dimensions of the social accountability pentagram [21][22] : policy makers (5), health administrators (4), family physicians (22 -20 involved with family medicine residency teaching, 2 not involved), other health professionals (6), family medicine residents (7) and members of public/patient (15). Participants were allowed to select multiple roles they belonged to, thus the total participant number does not equal that of the participants breakdown.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Overview of sample: A total of 57 participants initiated the survey, with 49 fully completing it, yielding a completion rate of 86%. The responders covered all dimensions of the social accountability pentagram [21][22] : policy makers (5), health administrators (4), family physicians (22 -20 involved with family medicine residency teaching, 2 not involved), other health professionals (6), family medicine residents (7) and members of public/patient (15). Participants were allowed to select multiple roles they belonged to, thus the total participant number does not equal that of the participants breakdown.…”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3][4] The lack of consistency in acquired skills can lead to unsatisfactory patient experience and outcomes, 1,5 as well as graduate doctors being more uncertain in their abilities. 1,2,6,7 One increasingly common method to enhance patient safety and the uniformity of learned skills in graduating medical residents is to incorporate Entrustable Professional Activities (EPAs) into a Competency-based Medical Education (CMBE) framework. [8][9][10][11] CBME is an outcomes-based approach structuring a medical education program using an organized framework of competencies (e.g.…”
mentioning
confidence: 99%
“…4,5 Ideally, an EPA framework should consist of a set of support documents or templates that provide guidance to researchers and educators when developing the EPA statements. 7 Development of an EPA framework also relies on educational institutions and workplace requirements aligning. 2 One study reports that adaptive workplaces and quality trained organisations have demonstrated successful development of an EPA framework.…”
Section: Introductionmentioning
confidence: 99%
“…There are a number of benefits of replacing time‐based apprenticeship models, in which competence is assumed following a set period, with an EPA approach in which documented evidence for skill acquisition is required to advance 4 . From a patient safety perspective, EPAs are meant to ensure that early health professionals can deliver safe patient care rather than simply assuming it; EPAs provide entry‐level health professionals with a clear understanding of the activities they are expected to perform and what competencies are required to advance to the next stage of training; they can also provide early health professionals with the confidence to seek assistance when they encounter unfamiliar tasks or situations.…”
mentioning
confidence: 99%
“…First and foremost, EPAs must be supported by evidence that they constitute meaningful descriptions of the activities performed by the early health professional 5 . Unfortunately, this has been identified as a weakness for some EPAs 1,6‐8 despite there being a wide variety of methods reported for doing so (eg surveys to assess whether the EPAs are an accurate reflection of work activities, 4,9 review of entry‐level job descriptions 10 ). At their heart, EPAs provide a stimulus for work analysis that can help identify and define the tasks performed by early health professionals 5 .…”
mentioning
confidence: 99%